Orthodontic problems in patients with Down syndrome from infancy to maturity based on own observations - Młynarska Zduniak, Elżbieta; Zadurska, Małgorzata; Siemińska –Piekarczyk, Barbara (Journal of Stomatology, 2015)
Introduction. The study presents orthodontic problems in children with Down syndrome from infancy to maturity based on the 12-year experience of the authors. Aim of the study. To analyse some abnormalities of the stomatognathic system in different periods of the to development of patients with Down syndrome and present these disorders in the light of findings of other authors who examined children without this syndrome. Material and methods. The study included 284 patients at different developmental age, treated at the Department of Orthodontics in the years 2007-2014. The patients were divided into six age groups. Diagnostic models, photographs and X-ray images and the information from the medical history were analyzed. The evaluation included malocclusion, parafunctions, dysfunctions and agenesis of the permanent teeth. Results. The relations of the gingival ridge were correct until the eruption of the first deciduous teeth in 66% of the study group. The eruption of deciduous teeth in the first year of life was observed in 31% of patients. 71.2% of the study toddlers had prognathism of the gingival ridge. In early childhood, 81% of patients had malocclusion, 94% dysfunctions and 65% parafunctions of the masticatory system. In late childhood, there were 97% cases of malocclusion, 90% of dysfunctions and 65% of parafunctions. In adolescence, 100% of patients had malocclusion, 58% parafunctions and 100% dysfunctions. In patients over 7 years, 31% were diagnosed with agenesis of the permanent teeth. Conclusions. The stomatognathic system disorders in patients with Down syndrome are present at all stages of development resulting in the need for the orthodontic treatment from birth to adulthood. These abnormalities are more common in children with Down syndrome than in children without it.